Impact of colloidal stabilization of MnZn-ferrite nanoparticles by oleic acid on their magnetothermal properties - Liu, N. N.; Alekhina, Yu. A.; Pyatakov, A. P.; Zharkov, M. N.; Yakobson, D. E.; Pyataev, N. A.; Sukhorukov, G. B.; Perov, N. S.; Tishin, A. M. (Frontiers in Thermal Engineering, 2023)
The development of magnetic agents for magnetic fluid hyperthermia application is the complex task requiring simultaneous optimization of chemical, biomedical, magnetic and, in particular, magnetothermal properties of magnetic nanoparticles(MNPs). In the majority of papers the magnetothermal measurements are carried out on bare MNPs suspended in deionized water with subsequent optimization of required physiological and medical properties including toxicity and biocompatibility. However in real hyperthermia practice the stable fluids or colloids of magnetic MNPs are used and the colloidal stabilization can significantly modify their magnetic properties including magnetothermal ones. This paper is focused on the study of ZnxMn1-xFe2O4 MNPs stabilized by oleic acid/sodium oleate in this context. Our research demonstrates the crucial changes in magnetic properties and magnetothermal response of ZnMn ferrite MNPs after the colloidal stabilization: while bare MNPs demonstrate the significant coercivity, nonzero remanent magnetization, and superquadratic dependence of heat generation on magnetic field, the magnetic properties of colloidal ZnMn ferrite MNPs are typical for superparamagnetic ones and their magnetothermal response is described by a conventional quadratic dependence on magnetic field amplitude. Various factors such as size distribution, magnetic anisotropy, interparticle dipole-dipole interaction are considered as the origins of such an impact on magnetic MNPs properties.